Preparation, Characterization and Antibacterial Effects of GC/PEG Nanocomposites Containing Silver Nanoparticles - Liu, Yangshuo; Yu, Fucheng; Liu, Lina (Asian Journal of Chemistry, 2012)
Novel nanocomposites consisting of genipin cross-linked chitosan (GC), poly(ethylene glycol) (PEG) and silver nanoparticles showed high antibacterial activity and were suitable for wound dressing. Various amounts of silver nanoparticles were added to GC/PEG matrix improve the film properties of nanocomposites. Water uptake ratios, antibacterial activity and cell culture of nanocomposite films were studied depending on the content of silver nanoparticles. With the increase of silver nanoparticles content, the water uptake ratios and the antibacterial activity of nanocomposite films were improved. Silver nanoparticles had the dual functions of uptake water and enhancing antimicrobial activity. Incorporation of silver in the GC/PEG matrix allowed the GC/PEG/silver nanocomposite to be applied successfully as the wound-healing materials.